Evaluation of the Antibacterial Activity of Cyperus rotundus Extract (An in vitro study) - Ghada Younis Abdul-Rahman; Aveen Hawal Rasoul (مجلة التربية والعلم, 2006)
The Cyperus rotundus tubers are commonly used in folk medicine in many countries as antiparasitic antidepressive and etc ...... The antibacterial effect of the aqueous extracts of this plant was evaluated using selected Gram positive and Gram negative bacteria and microdilution technique. The results showed a significant inhibitory effect of 10-2 and 10-3 dilutions of the aqueous extract on all the tested Gram negative but not the Staphylococcus aureus. Key Words: Cyperus rotundus, antimicrobial activity.